AST to platelet ratio index for predicting the in hospital mortality in chronic liver disease patients in tertiary care hospital (Asian Journal of Medical Sciences, 2019)
Background: Liver cirrhosis is the end result of chronic liver injury. Cirrhosis of liver may progressively deteriorate from a well-compensated state to decompensated conditions.Aims and Objective: Our study aims at evaluating the AST to Platelet Ratio Index (APRI) for predicting the in-hospital mortality and also comparing APRI, MELD and albumin for predicting in hospital mortality in chronic liver disease.Materials and Methods: Data of Patients with Chronic liver disease were retrospectively reviewed. MELD and APRI scores were calculated for the patients and results from ROC curves were analysed.Results: In our study conducted on 299 patients, the age distribution was between 18-64 years with mean age of patients being 46.47+/-10.9 years, sex ratio Male: Female: 266:37 with mortality rate of 17.7%. The area under curves of ROC of APRI, MELD and Albumin are 0.63, 0.76 and 0.55.Conclusion: APRI is an independent predictor of mortality. The prognostic performance of all 3 was comparable but MELD has better prognostic significance than APRI score.